DISEMINASI PENINGKATAN KAPASITAS PENGELOLA BUMDES DAN UMKM DI KECAMATAN GEGERBITUNG - Arrina Lestari, Nurni; Khairul Amal, Muhammad; Siwiyanti, Leonita (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2022)
Village development is a priority in national development, one way is by building BUMDes and MSMEs to develop village potential with the aim of improving community welfare. Government assistance in the form of village funds is provided to achieve this goal. However, as time goes by, many BUMDes and MSMEs are unable to develop even to the point of stalling. The method of implementing this community service activity is carried out with the stages of observation, training, and mentoring. Based on observations, it was found that some BUMDes managers did not develop businesses based on village potential and there was still a lack of knowledge of village managers about BUMDes. Furthermore, at the training stage, it resulted in an increase of 57% in the understanding of BUMDes and MSME managers. However, in terms of assistance, it is very necessary to have support from regional leaders so that further training needs to be improved, especially in increasing human resources so that good regeneration of BUMDes and MSMEs management is needed in the Gegerbitung District, Sukabumi Regency.